USING LITERATURE TO INFORM VIGNETTES DESIGNED TO EXPLORE THE PERCEPTIONS OF IMPLANTABLE CARDIOVERTER DEFIBRILLATOR (ICD) DEACTIVATION AT END OF LIFE. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Hill, Loreena; McIlfatrick, Sonja; Taylor, Brian; Fitzsimons, Donna
Abstract : Background: Rates of ICD implantation are increasing and while international documents guide professionals on the management of patients with an ICD, recent evidence illustrates disparity in the application of guidelines to practice. Furthermore limited research on patient preferences and lack of clarity on the ICD's role at end of life are compromising the provision of optimal care. Aims: A systematic review of evidence published between 2008 and 2013. Methods: A generic search strategy was developed, based on twelve key terms which were refined through an iterative process involving articles retrieved in a preliminary scoping review. Six electronic databases were selected and the search strategy adapted and applied. Studies were included if they met the inclusion criteria- Empirical studies published in English Language; primarily related to adults (above 18 years) with an implanted ICD; primarily related to the deactivation of ICDs at end of life. Citations and expert recommendation papers were checked for relevance. Quality of each study was assessed using the Hawker et al ., (2002) protocol and data were systematically extracted. Narrative synthesis led to the development of 3 key themes and identification of the salient factors or independent variables (IVs) in the ICD deactivation decision. Results: Within the literature there is considerable variation in patients' preferences concerning ICD deactivation. These were grouped under three themes- preferences for the discussion, the ethical and legal considerations and facing the future. The validity of this evidence will be further refined through qualitative exploration involving patients, carers and professionals to determine the most appropriate IVs to generate vignettes for a UK wide professional factorial survey. Conclusions: This innovative factorial survey design combines qualitative exploration and quantitative survey techniques. Greater understanding of decision-making in this complex setting will contribute to the development of appropriate educational support and improved care for ICD patients approaching end of life.